Proxima due : Instituto Italiano di Cultura Berlin in Zusammenarbeit mit 'Associazione Dante Alighieri'. - Fagone, Vittorio; Di Mauro, Alberto; Associazione 'Dante Alighieri', Berlin (Berlino : Instituto Italiano di Cultura, 1994)
Bianchi, Francesca ; Bottinelli Montandon, Mario ; Palazzi, Emanuela ; Palerma, Federico ; Ragni, Lucilla ; Tomasi, Elisa ; Zappa, Marco.
'Dante Alighieri', Berlin, 28 September - 4 Oktober 1994
kunstcatalogus